Psychological well-being of students is the leading trend of contemporary e-pedagogics - Yu. S. Zinchenko; V. V. Gusarenko (Вестник университета, 2022)
The article presents the results of the study aimed at identifying the level of influence of distance learning on the psychological well-being of students. The objects of the study are the environment and factors having a negative impact on the psychological well-being in the student environment of the Krasnoyarsk State Medical University named after Professor V.F. Voyno-Yasenetsky. In order to explore the main challenges of digital pedagogy, a questionnaire survey of 140 second year students of the medical, pediatric and dental faculties of the university was carried out. The results of the survey have demonstrated that distance learning had a negative impact on the rhythm of students’ classes, negatively affected the level of student responsibility in the educational process and the causes of emotional burnout. During remote classes, the conflict between students decreased, and along the line of student-teacher interaction, on the contrary, it increased. The results of the study may be of interest both to the management of universities and to the teaching staff, since the distance format is being introduced into the usual learning activities of students.